Enhanced Thermal Stability in Dielectric Properties of NaNbO3 –Modified BaTiO3 –BiMg1/2 Ti1/2 O3 Ceramics for X9R-MLCC Applications - Muhammad, Raz (2022)
0.5BaTiO3 –(0.5 − x)BiMg1/2 Ti1/2 O3 –xNaNbO3 (x = 0.10–0.30) ceramics were processed via a conventional solid state sintering route. X-ray diffraction analysis and Raman spectroscopy showed the formation of a cubic perovskite structure. Microstructural analysis of the samples revealed densely packed grains. The addition of NaNbO3 resulted in the enhancement in dielectric properties as a function of temperature. Relative permittivity decreased from 850 to 564 (at room temperature) with an increase in x; however, the stability in dielectric properties was improved with an increase in NaNbO3 concentration. At x = 0.25, relative permittivity (εr ) was ~630 ± 15% in a temperature range of −70–220◦ C with low dielectric loss (tan δ) < 0.025 (−57 to 350◦ C) and high recoverable energy density ~0.55 J/cm3 which meet the criterion for X9R MLCC applications.